The appropriate expression and coordination of glycolate oxidase and catalase are vital to the successful construction of the photorespiratory metabolic pathway - Yao, Zhen; Rao, Zelai; Hou, ShuWang; Tian, Changwei; Liu, Chun-Yan; Yang, Xiulan; Zhu, Guicai (Frontiers in Plant Science, 2022)
Photorespiration has emerged as a hotspot in the evolution of photosynthesis owing to the energy loss during the process. To ensure the physiological functions of photorespiration such as light protection, H2O2 signaling, and stress resistance, separate the photorespiration glycolic acid flow, and minimize photorespiration loss, a balance must be maintained during the construction of photorespiratory metabolic branch. In this study, glycolate oxidase (GLO) and catalase (CAT) were introduced into potato (Solanum tuberosum) chloroplasts through the expression of fusion protein. Through the examination of phenotypic characteristics, photosynthesis, anatomical structure, and enzyme activity, the efficiency of the photorespiration pathway was demonstrated. The results showed that certain transgenic lines plants had shorter plant height and deformed leaves and tubers in addition to the favorable photosynthetic phenotypes of thicker leaves and larger and denser mesophyll cells. By Diaminobenzidine (DAB) staining analysis of the leaves, the intermediate H2O2 could not be decomposed in time to cause biomass decline and malformation, and the excessive glycolate shunt formed by the overexpression of the fusion protein affected other important physiological activities. Hence, the appropriate and coordinated expression of glycolate oxidase and catalase is essential for the establishment of photorespiration pathways in chloroplasts.